2021
DOI: 10.1136/gutjnl-2021-324767
|View full text |Cite
|
Sign up to set email alerts
|

Influence of timing of maternal antibiotic administration during caesarean section on infant microbial colonisation: a randomised controlled trial

Abstract: ObjectiveRevised guidelines for caesarean section (CS) advise maternal antibiotic administration prior to skin incision instead of after umbilical cord clamping, unintentionally exposing the infant to antibiotics antenatally. We aimed to investigate if timing of intrapartum antibiotics contributes to the impairment of microbiota colonisation in CS born infants.DesignIn this randomised controlled trial, women delivering via CS received antibiotics prior to skin incision (n=20) or after umbilical cord clamping (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 66 publications
6
26
1
Order By: Relevance
“…In this analysis, we uncover further nuances. Safety of one to two courses of antibiotics towards offspring IBD risk is consistent with data on lack of microbiome disruption 1. For further courses, benefits should be weighed against risks.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…In this analysis, we uncover further nuances. Safety of one to two courses of antibiotics towards offspring IBD risk is consistent with data on lack of microbiome disruption 1. For further courses, benefits should be weighed against risks.…”
supporting
confidence: 67%
“…We read with interest the randomised controlled trial by Dierikx et al that demonstrated the lack of long-term impact of antenatal antibiotics on offspring gut microbiome 1. Antibiotics in early life are implicated in IBD risk, potentially mediated by gut microbiome perturbations and altered host–microbe interactions 2 3.…”
mentioning
confidence: 99%
“…We cannot ascertain use or timing of peripartal antibiotic prophylaxis in our maternal cohort, but a randomized control trial including 20 children in each arm with up to 3 years of follow-up failed to show any effect of different timing of antibiotic treatment, although both groups differed compared with a third group of vaginally delivered children. These findings indicate that there are other more important factors that explain the association of caesarean section with the child’s gut microbiota 48 .…”
Section: Discussionmentioning
confidence: 74%
“…We know that caesarean section has a profound effect on the gut microbiota, and it may be that a single dose of prophylactic antibiotics does not have further significant impact on what is already a dysbiosis. This is supported by two small recent randomised controlled trials that did not find marked differences in microbial colonisation in babies exposed to cefuroxime administered before skin incision compared with babies with caesarean birth whose mothers received antibiotics after cord clamping 45…”
mentioning
confidence: 82%